A NEW APPROACH TO HOLISTIC NITROGEN MANAGEMENT IN CHINA - Xuejun LIU, Zhenling CUI, Tianxiang HAO, Lixing YUAN, Ying ZHANG, Baojing GU, Wen XU, Hao YING, Weifeng ZHANG, Tingyu LI, Xiaoyuan YAN, Keith GOULDING, David KANTER, Robert HOWARTH, Carly STEVENS, Jagdish LADHA, Qianqian LI, Lei LIU, Wim DE VRIES, Fusuo ZHANG (Frontiers of Agricultural Science and Engineering, 2022)
<ListItem><ItemContent> ● Progress on nitrogen management in agriculture is overviewed in China. </ItemContent></ListItem> <ListItem><ItemContent> ● 4R principles are key to high N use efficiency and low N losses in soil-crop systems. </ItemContent></ListItem> <ListItem><ItemContent> ● A new framework of food-chain-N-management is proposed. </ItemContent></ListItem> <ListItem><ItemContent> ● China’s success in N management provides models for other countries. </ItemContent></ListItem> Since the 1980s, the widespread use of N fertilizer has not only resulted in a strong increase in agricultural productivity but also caused a number of environmental problems, induced by excess reactive N emissions. A range of approaches to improve N management for increased agricultural production together with reduced environmental impacts has been proposed. The 4R principles (right product, right amount, right time and right place) for N fertilizer application have been essential for improving crop productivity and N use efficiency while reducing N losses. For example, site-specific N management (as part of 4R practice) reduced N fertilizer use by 32% and increased yield by 5% in China. However, it has not been enough to overcome the challenge of producing more food with reduced impact on the environment and health. This paper proposes a new framework of food-chain-nitrogen-management (FCNM). This involves good N management including the recycling of organic manures, optimized crop and animal production and improved human diets, with the aim of maximizing resource use efficiency and minimizing environmental emissions. FCNM could meet future challenges for food demand, resource sustainability and environmental safety, key issues for green agricultural transformation in China and other countries.